(untitled) (Historia, 2021)
During May 196 the Natal Archives received one of the more valuableaccessions ever received by an Archive j depot in the country namely, thecontents q the Library of .the Natal Provincial Council, totalling some14,200 items in all. It is a library."of upcommo interest to the research-worker in a large numb r of fields, but particul cly in that of historicalinvestigation.The intention of. the Natal Legislative Council was to build up a com-plete library -reference section and all -and so books covering allaspects of life in which legislators might conceivably be interested wereordered from England and bound there in leather before being shipped toNatal. The Legislative Council, and later the Natal Parliament, voted anannual sum of money for its upkeep until Union in 1910; after 1910 thiswas discontinued but all government publications were sent to the libraryfor the purposes of record.The result is that the Library is, as a visiting librarian remarked envi-ously "both a museum-piece and a window on the Victorian and Edwardianworlds." Captured within it is the world as the "Victorian and the Edwardiansaw it. For as many aspects as it was possible to encompass within theconfines of a fairly small reference library are represented here. Thereare books on: Fiction, Essays, Letters, Biographies, Geography, Geology,Anthropology, Entymology, History (Ancient and Modern), Useful Arts,Fine Arts, Architecture, Agriculture, Botany, Law, Tribal Wars, Religion,Politics, Dictionaries, Who’s Who (British and South African), South Africanand Overseas Directories, Railway Engineering, Poetry, Literature, Encyclo-paedias and Periodicals, to mention a few taken at random. There is ofcourse a host of other subjects as well.Perhaps the best description of the library was given in 1955, when itwas reported to consist of: Statutes, Votes and Proceedings, etc. (of S.A.,U.K. and other countries), Reports of Committees, Blue Books, Directories,Whitaker’s, Who’s Who, Law Books, etc., also much biography, some travel,Africana, hobbies, agriculture, natural science, sociology, etc., much fiction,poetry, essays, etc